Rekonstruksi Peran MGMP dalam Pendidikan Islam: Penguatan Kompetensi Guru PAI di Sekolah Menengah - Abd Mannan; Saiful Arif; Zainol Hasan; Mad Sa’i; Yunia Nabila Aziziy; Suwantoro (Rabbani: Jurnal Pendidikan Agama Islam, 2026)
This study explores the impact of MGMP PAI activities on teacher competency at the junior high school level in Pamekasan Regency. The participants include MGMP board members and teacher members. A qualitative phenomenological approach was applied, with data collected through interviews, observation, and documentation. Data were analyzed using the Miles and Huberman model. The findings show that MGMP activities enhance pedagogical, professional, social, and personal competencies. Through workshops, discussions, and classroom observation, teachers develop teaching skills, deepen content knowledge, and foster creativity. MGMP serves as a collaborative learning space that promotes continuous professional growth in Islamic Religious Education.